Impact of empowering leadership on adaptive performance in hybrid work: a serial mediation effect of knowledge sharing and employee agility - Seung-Seok Kim; Dong-Yeol Yoon (Frontiers in Psychology)
With the advent of the pandemic era, many organizations have implemented a hybrid work model to manage office- and remote-based work. The proliferation of hybrid work demands leaders to demonstrate a different style of leadership than that in the past and to delegate authority, providing autonomy and responsibility to employees. Furthermore, both within and outside the organization, members must adapt and respond to rapidly changing environments and demonstrate adaptive performance to generate better outcomes. This study identifies the relationship between empowering leadership and adaptive performance in hybrid work, based on the social exchange and self-determination theories. Furthermore, it validates the mediation effect of knowledge sharing and employee agility and serial mediation effect. We analyzed data from 290 IT manufacturing employees working in hybrid work in South Korea. The findings reveal that empowering leadership positively influences adaptive performance and that knowledge sharing and employee agility partially mediate this relationship. Moreover, knowledge sharing and employee agility serially mediate the impact of empowering leadership on the adaptive performance of employees. These research findings provide theoretical and practical implications for organizations in hybrid work.